A tale of highly unusual magic - Papademetriou, Lisa (Harper, an imprint of HarperCollinsPublishers, 2015)
"Two girls on opposite sides of the planet connect through a mysterious book, whose phantom narrator guides them into spinning a story about the past that will affect their futures"--